Quilombos e quilombagem no ensino de História: estudo sobre a contribuição paradidática de Clóvis Moura - Malanga, Suzane Jardim [UNIFESP] (2019)
The objective of this research is to discuss some possibilities of insertion of the themes related to quilombos, as the main form of resistance to slavery, in the teaching of history. Our study is based on the contributions of Clóvis Moura present in his work of reference, the book Rebeliões da senzala: quilombos, insurreições, guerrilhas and in two author paradidate works published between 1987 and 1993: Quilombos – resistência ao escravismo and História do negro brasileiro. The latter have been published in a context in which the black movement comes to the public to demand a new reading about the Brazilian slaveholding past while the market for paradidate books reaches its apex. In this way, our intention is to analyze the actions of the black movement in the context of the 1970s and 1980s, in the light of the contributions of Nilma Lino Gomes, and their impact on the editorial field, historiographic and historical teaching. For the analysis of our sources, we turn to the contributions of Norman Fairclough and Critical Discourse Analysis in order to understand how the discourse present in Rebeliões da Senzala echoes in the paradidate books. Finally, we articulate the discussions raised during the first and second chapters to the teaching of history, raising some possibilities of work to the teaching of quilombos history in the perspective of valuing the history of the Afro-Brazilian population and the fight against racism.